Clinical and molecular analysis of a four-generation Chinese family with aminoglycoside-induced and nonsyndromic hearing loss associated with the mitochondrial 12S rRNA C1494T mutation - Wang, Qiuju; Li, Qing-Zhong; Han, Dongyi; Zhao, Yali; Zhao, Lidong; Qian, Yaping; Yuan, Hu; Li, Ronghua; Zhai, Suoqiang; Young, Wie-Yen; Guan, Min-Xin (Biochemical and biophysical research communications, 2006)
We report here the clinical, genetic, and molecular characterization of a four-generation Chinese family with aminoglycoside-induced and nonsyndromic hearing loss. Five of nine matrilineal relatives had aminoglycoside-induced hearing loss. These matrilineal relatives exhibited variable severity and audiometric configuration of hearing impairment, despite sharing some common features: being bilateral and having sensorineural hearing impairment. Sequence analysis of mitochondrial DNA (mtDNA) in the pedigree identified 16 variants and the homoplasmic 12S rRNA C1494T mutation, which was associated with hearing loss in the other large Chinese family. In fact, the occurrence of the C1494T mutation in these genetically unrelated pedigrees affected by hearing impairment strongly indicated that this mutation is involved in the pathogenesis of aminoglycoside-induced and nonsyndromic hearing loss. However, incomplete penetrance of hearing loss indicated that the C1494T mutation itself is not sufficient to produce a clinical phenotype but requires the involvement of modifier factors for the phenotypic expression. Those mtDNA variants, showing no evolutional conservation, may not have a potential modifying role in the pathogenesis of the C1494T mutation. However, nuclear background seems to contribute to the phenotypic variability of matrilineal relatives in this family. Furthermore, aminoglycosides modulate the expressivity and penetrance of deafness associated with the C1494T mutation in this family.